2015
DOI: 10.5812/jjm.19048
|View full text |Cite
|
Sign up to set email alerts
|

Efflux Pump Inhibitor Phenylalanine-Arginine Β-Naphthylamide Effect on the Minimum Inhibitory Concentration of Imipenem in Acinetobacter baumannii Strains Isolated From Hospitalized Patients in Shahid Motahari Burn Hospital, Tehran, Iran

Abstract: Background:Acinetobacter baumannii has emerged as a highly troublesome pathogen and a leading cause of mortality and morbidity among hospitalized burn patients.Objectives:The aims of this study were to determine the frequency of the AdeABC genes and the role of the efflux pump (s) in the imipenem resistance of A. baumannii strains isolated from burn patients.Materials and Methods:This study was conducted on 60 A. baumannii isolates collected from 240 wound samples of burn patients admitted to the Burn Unit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 18 publications
(25 reference statements)
2
12
0
Order By: Relevance
“…It was reported that the imipenem susceptibility of most A. baumannii isolated from burns was increased in the presence of the PAβN by 4 to 64 folds (14). Our results indicated the role of efflux pump mechanism in imipenem and meropenem resistance in A. baumannii isolates.…”
Section: The Role Of Adeabc Efflux Pump Genes In Multidrug and Carbapsupporting
confidence: 54%
See 1 more Smart Citation
“…It was reported that the imipenem susceptibility of most A. baumannii isolated from burns was increased in the presence of the PAβN by 4 to 64 folds (14). Our results indicated the role of efflux pump mechanism in imipenem and meropenem resistance in A. baumannii isolates.…”
Section: The Role Of Adeabc Efflux Pump Genes In Multidrug and Carbapsupporting
confidence: 54%
“…In another conducted study from Iran on 60 A. baumannii isolates from burn units, the results revealed the detection of adeA and adeB genes in all isolates (100%) while AdeC was present in 51 isolates (85%) (14). In another study by Hou et al (15) it was found that adeB, adeR, adeS, adeJ and abeM were found in the majority of imipenem resistant A. baumannii (> 80% …”
Section: Detection and Distribution Of Adeabc Efflux Pump Genesmentioning
confidence: 91%
“…The nosocomial infections, caused by multidrug-resistant (MDR) bacteria, are one of the most important causes of mortality throughout the world (3). Therefore, multidrug-resistant Gram-negative rods will be a serious problem if no adequate action is taken (4,5). Unfortunately, the issue of antibiotic resistant bacteria in Iran is increasing, following the rising trend of its global counterpart (6).…”
Section: Contextmentioning
confidence: 99%
“…For every carbapenemase activity, the sensitivity and specificity of it is 100% and 98.5%, respectively. In addition, this method has the accuracy to differentiate carbapenemase producers from non-carbapenemase producers, among carbapenem-nonsusceptible isolates [extended spectrum beta-lactamases (ESBLs), cephalosporinase producers and fault in outer 4 Arch Clin Infect Dis. 2016; 11(2):e32816.…”
Section: Ultraviolet Spectrophotometermentioning
confidence: 99%
“…Fallah et al reported that the resistance to colistin was found in two A. baumannii strains (1.8%) (16). Gholami et al reported no resistance to colistin among the A. baumannii strains (19). Therefore, colistin could be useful in curing infections that A. baumannii cause, mainly in burn patients.…”
Section: Discussionmentioning
confidence: 99%